PERANCANGAN BUKU FOTOGRAFI PASAR TRADISIONAL BERBASIS HUMANISME SEBAGAI UPAYA MENYADARAKAN EMPATI REMAJA SURABAYA - Rianugrah, Prisantyo Dwi; budiardjo, hardman; cinantya, ixsora gempita (Jurnal Art Nouveau, 2017)
Traditional market has been one of Indonesian nation culture. Traditional market is not a difficult thing to find its existence including the city of Surabaya. Many lessons can be learn in the activities that exist in traditional markets, one of them in terms of humanism. But now teenagers is very rarely to visit traditional markets, especially in the Surabaya. Traditional market has own uniqueness that can be a learning for the people, especially teenagers. Therefore, this research is intended for the create of humanism-based photography book as an effort to awaken the empathy of Surabaya teenagers. The teenagers will be the next generation, so as to maintain the existence of traditional markets and workers for the future. In this study authors use a qualitative research methodology that emphasizes the aspect of understanding a problem rather than looking at the problem for generalization research. This research method prioritizes in-depth analysis techniques, examines the problems in one case because qualitative methodology knowing that the character of a problem will be different from the character of the other problem. The results of this photography book is expected people, especially teenagers can bring a sense of empathy and appreciate their efforts, especially the traditional market workers who became the object of this research.Keywords: Traditional Market, Humanism, Photography, Empthy